Conformational transitions induced by in vitro macromolecular crowding lead to the amyloidogenesis of buffalo heart cystatin. Issue 12 (18th June 2015) - Sohail, Aamir; Bhat, Sheraz A.; Siddiqui, Azad A.; Zaman, Masihuz; Khan, Rizwan H.; Bano, Bilqees
Abstract : The biological cells and extracellular matrix exhibit a highly crowded environment, called as macromolecular crowding. Crowding significantly influences protein structure and may lead to its aggregation. In the present study, buffalo heart cystatin (BHC), after purification from buffalo heart tissue, has been used as a model protein for studying effect of macromolecular crowding in the presence of high concentrations of bovine serum albumin (BSA), poly‐ethylene glycol‐1000 (PEG‐1000), and poly‐ethylene glycol‐4000 (PEG‐4000). Cystatins are thiol protease inhibitors and found to be involved in various important physiological processes. Functional inactivation of BHC was observed upon crowding, which varied as a function of concentration and molecular weight of crowding agents as well as incubation time. Structural changes of BHC at tertiary and secondary level were detected with the help of fluorescence and CD spectroscopy. CD analysis showed changes of α‐helix to β‐sheet, which could be due to aggregation. The ANS‐fluorescence study suggested the unfolding and presence of some partially folded intermediates. Increase in ThT‐fluorescence and absorption of Congo red spectra with red shift, confirmed the amyloid type aggregation of BHC in the presence of various crowding agents. Finally, electron microscopy provided the physical evidence about the formation of amyloid fibrils. Results suggested that among the various crowding agents used, amyloidogenesis of BHC was maximal in case of BSA followed by PEG‐4000 and least for PEG‐1000. The present work makes an important contribution in crowding mediated protein aggregation, which can have implications of potential interest. Copyright © 2015 John Wiley & Sons, Ltd.